2001
DOI: 10.1074/jbc.m103298200
|View full text |Cite
|
Sign up to set email alerts
|

Functional Interaction of p53 and BLM DNA Helicase in Apoptosis

Abstract: The Bloom syndrome (BS) protein, BLM, is a member of the RecQ DNA helicase family that also includes the Werner syndrome protein, WRN. Inherited mutations in these proteins are associated with cancer predisposition of these patients. We recently discovered that cells from Werner syndrome patients displayed a deficiency in p53-mediated apoptosis and WRN binds to p53. Here, we report that analogous to WRN, BLM also binds to p53 in vivo and in vitro, and the C-terminal domain of p53 is responsible for the interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
102
1
1

Year Published

2001
2001
2009
2009

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(111 citation statements)
references
References 51 publications
6
102
1
1
Order By: Relevance
“…We observed only partial checkpoint defects in him-6 C. elegans worms. Similarly, irradiation-induced apoptosis and G 2 /M cell cycle arrest is only partially compromised in human BS Ϫ/Ϫ cells (1,59). It was recently shown that HIM-6 physically interacts with the C. elegans ATR homolog, whose inactivation by RNAi leads to defective checkpoint processes in response to ionizing radiation (8), as well as to HU (A. Gartner, unpublished observation).…”
Section: Discussionmentioning
confidence: 99%
“…We observed only partial checkpoint defects in him-6 C. elegans worms. Similarly, irradiation-induced apoptosis and G 2 /M cell cycle arrest is only partially compromised in human BS Ϫ/Ϫ cells (1,59). It was recently shown that HIM-6 physically interacts with the C. elegans ATR homolog, whose inactivation by RNAi leads to defective checkpoint processes in response to ionizing radiation (8), as well as to HU (A. Gartner, unpublished observation).…”
Section: Discussionmentioning
confidence: 99%
“…86 BS cells also appear defective in p53-dependent apoptosis following artificial overexpression of p53. 87 However, such a connection to damage-induced apoptosis may not be significant under normal circumstances since BS cells remain exquisitely sensitive to alkylating agents. 82 WRN is another RecQ family helicase that has been linked to the rare genetic disease Werner's syndrome (WS).…”
Section: Autosomal Recessive Predisposition To Cancermentioning
confidence: 99%
“…Nevertheless, in vitro studies demonstrate that P53 binds both ss and dsDNA (Oberosler et al, 1993;Bakalkin et al, 1994), possesses a 3 0 -5 0 exonuclease activity and promotes DNA reannealing (Oberosler et al, 1993;Mummenbrauer et al, 1996). Furthermore, P53 also binds to mismatches and three-stranded DNA substrates (Lee et al, 1995;Dudenhoffer et al, 1998), and to Holliday junctions, thereby facilitating their resolution (Lee S et al, 1997); complexes with and inhibits RAD51 (Sturzbecher et al, 1996;Buchhop et al, 1997); interacts with BRCA2 (Marmorstein et al, 1998); complexes with BLM and WRN (Blander et al, 1999;Spillare et al, 1999;Wang XW et al, 2001); and regulates the BLM and WRN helicase activities on Holliday junctions in vitro (Blander et al, 1999;Spillare et al, 1999;Wang XW et al, 2001;Yang et al, 2002b). Ectopic overexpression of wild-type P53 suppresses HRR on extrachromosomal and chromosomal DNA substrates .…”
Section: Role Of P53 and Other Tumor Suppressors In Dsb Repairmentioning
confidence: 99%